Case Report: Phenotypic heterogeneity within an NF1 family: assessment of the pathogenicity of a de novo c.6640dupA shift mutation and a splice variant with an epilepsy phenotype - Ren, Sijing; Wang, Yanling; Tong, Xinhua; Wu, Xiaoyu; Yan, Huan; Kong, Qing-Xia (Frontiers in Neuroscience, 2025)
PurposeNeurofibromatosis type 1 (NF1) is a complex autosomal dominant disorder with wide variability in its clinical presentation, rate of progression, and severity of complications. The majority of patients have point mutations, but no specific mutational hotspots have been identified. The aim of the present study was to better understand the genotypic and phenotypic characteristics of NF1 by conducting a detailed analysis of a single case, from genetic diagnosis to the exploration of underlying mechanisms.MethodsThe study included an 11-year-old girl with epilepsy who presented to our hospital in 2021. Clinical data of the patient and her family members were collected, and peripheral venous blood samples were analyzed for causative genes using whole-exome sequencing. The identified genes were validated using Sanger sequencing, and alterations in the tertiary structural physicochemical properties of the mutant proteins were analyzed using AlphaFold2 bioinformatics software.ResultsWe identified two mutation sites in the NF1 gene of the patient. A heterozygous c.6640dupA mutation that leads to an amino acid shift (p.R2214Kfs*7) was inherited from the mother. This mutation site is new and has not been previously reported. Despite having the same mutation, the patient had seizures with a completely different clinical presentation than that of her mother, who had had intracranial tumors. This finding prompted us to consider potential differences in genotype–phenotype correlations in this NF1 family line. The other identified mutation, a heterozygous c.7395-3C > G mutation that results in amino acid splicing, was inherited from the patient’s father. Although the father carried the mutation, he did not have any related manifestations. We therefore suspected that the mutation at this locus was not pathogenic, a suspicion we confirmed in the patient’s brother.ConclusionIn the present study, we not only identified previously undescribed de novo mutations in NF1 but also contributed to a broader understanding of the NF1-related NF1 gene profile. Our findings have implications for the molecular diagnosis of the disease and the development of effective therapeutic approaches.